2018
DOI: 10.1371/journal.pone.0198118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the inter-observer variability of Computer-Aided Nodule Assessment and Risk Yield (CANARY) to characterize lung adenocarcinomas

Abstract: Lung adenocarcinoma (ADC), the most common lung cancer type, is recognized increasingly as a disease spectrum. To guide individualized patient care, a non-invasive means of distinguishing indolent from aggressive ADC subtypes is needed urgently. Computer-Aided Nodule Assessment and Risk Yield (CANARY) is a novel computed tomography (CT) tool that characterizes early ADCs by detecting nine distinct CT voxel classes, representing a spectrum of lepidic to invasive growth, within an ADC. CANARY characterization ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Previously, CANARY has been validated to have very low degree of interobserver variability, even among novice users. 18 However, the interobserver reproducibility of SILA computation with use of the aforementioned semiautomated seed-growing algorithm was evaluated by Bland-Altman plot of two observers independently segmenting 45 separate AC nodules. The interrater reliability of the categorization based on SILA thresholds was also assessed by using the linear weighted k.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, CANARY has been validated to have very low degree of interobserver variability, even among novice users. 18 However, the interobserver reproducibility of SILA computation with use of the aforementioned semiautomated seed-growing algorithm was evaluated by Bland-Altman plot of two observers independently segmenting 45 separate AC nodules. The interrater reliability of the categorization based on SILA thresholds was also assessed by using the linear weighted k.…”
Section: Discussionmentioning
confidence: 99%
“…A Kappa score of 0.61-0.80 signifies significant agreement and 0.81-1.00 signifies perfect agreement. Our group concluded that with adequate training, CANARY can be widely applied with reproducible results (23). Additional internal validation among three independent users (B Bartholmai, R Karwoski, S Rajagopalan) for 283 adenocarcinomas from Mayo historical cases again showed excellent ICC for all exemplars and the summed V-I-R-O category ( Table 2).…”
Section: Interobserver Agreementmentioning
confidence: 79%
“…In this study, we evaluated the versatility of CANARY by applying Korean patients. CANARY has been developed through constant validation on various users and institutions, but still has a limitation that it has only been verified in American and European patients [4][5][6][7][8][9]. This study is of great significance in that it was able to validation CANARY on Asian patients for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-Aided Nodule Assessment and Risk Yield (CANARY), which is based on a machine learning technique, is one of the most advanced types of software. It has been steadily improved, and its performance has been verified through previous studies [4][5][6][7][8][9]. CANARY divides semi-auto segmented GGN regions of interest into nine distinct exemplars based on radiomic features and clusters them into three separate groups for risk stratification.…”
Section: Introductionmentioning
confidence: 94%